Nilai-Nilai Edukatif Dalam Novel Tirani Dedaunan Karya Chairul Al-Attar: Tinjauan Sosiologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra Indonesia Di SMA - HASTINI, Hastini; , Dr. H. Nafron Hasjim (2016)
The purpose of this study is (1) to describe the structure of the building novel Tyranny Foliage works Chairul al-Attar, (2) describe the educational values that exist in the novel Tyranny Foliage works Chairul al-Attar, (3) describe the implementation of novel Tyranny Foliage works Chairul al-Attar as teaching materials Indonesian literature at the high school. The method used is qualitative descriptive. The object of this research is the educational values embodied in the novel Tyranny Foliage works Chairul al-Attar. The data used are sentences, and paragraphs that contain educational values in the novel Tyranny Foliage works Chairul al-Attar. Sources of primary data in this study is novel Tyranny Foliage works Chairul al-Attar. As for the secondary data in this study is the article, the reviewer novel related to novel Tyranny Foliage works Chairul al-Attar. Data collection techniques using literature techniques and see-note technique. The validity of the technique used in this research is data triangulation. Based on the structural analysis, the theme of the novel Tyranny of the foliage is three companions migrated to Jogja: Fatah, Zaenal, and Rian. All three underwent full days of battle of life. Flow used in novel Tyranny foliage is advanced groove. Figures analyzed are Fatah, Zaenal, Rian, Indra and Mbak Endang, Ningsi, Nita, Goddess, Lisda. Background of the novel consists of a background TiraniDedaunan place, time setting, and social background. The results of the analysis of educational values found five educational value contained in the novel Tyranny of the foliage. Five educational value is 1) the value of honesty, 2) the value of responsibility, 3) the value of cooperation or mutual help, 4) the value of happiness, 5) the value of love and affection that includes (a) the value of the family, (b) love against God, (c) a love for others. The results of the study novel Tyranny Foliage works Chairul Al-attar can be implemented in the teaching of literature in high school, in accordance with the Standards of Competence 7 "understand the various tales, novels Indonesia / novels in translation" and the basic competencies 7.2 "to analyze the elements of intrinsic and extrinsic novel Indonesia / translation ". In the novel Tyranny Leaves are builders novel elements that can be analyzed by learners.